2019
DOI: 10.3389/fpsyg.2019.02026
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Stimulation Training With Technically Manipulated Musical Material in Preschool Children With Specific Language Impairments: An Explorative Study

Abstract: Auditory stimulation training (AST) has been proposed as a potential treatment for children with specific language impairments (SLI). The current study was designed to test this assumption by using an AST with technically modulated musical material (ASTM) in a randomized control group design. A total of 101 preschool children (62 male, 39 females; mean age = 4.52 years, SD = 0.62) with deficits in speech comprehension and poor working memory capacity were randomly allocated into one of two treatment groups or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
8
0
1
Order By: Relevance
“…Appendix B presents detailed tables with the characteristics of the included studies. Of the included studies, one was an SR [ 52 ] and 26 RCTs [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] (including two studies [ 86 , 87 ] derived from Loo et al’s [ 89 ] review) on the effectiveness of interventions for the treatment of identified DLDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Appendix B presents detailed tables with the characteristics of the included studies. Of the included studies, one was an SR [ 52 ] and 26 RCTs [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] (including two studies [ 86 , 87 ] derived from Loo et al’s [ 89 ] review) on the effectiveness of interventions for the treatment of identified DLDs.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 RCTs, six studies evaluated either expressive [ 63 , 64 , 65 , 66 , 67 ] or receptive [ 68 ] phonological skills, one on expressive vocabulary [ 69 ], eight grammar/morphological skills [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], with one reporting data on both phonological and morpho-syntactic skills [ 78 ], two on narrative skills [ 79 , 80 ]; two examined meta-phonological skills [ 81 , 82 ] and six language skills in general [ 83 , 84 , 85 , 86 , 87 , 88 ], including two [ 87 , 88 ] comparing the effectiveness of the “Fast ForWord Language” (FFW-L) training program with other intervention programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the relative lack of conclusive findings in the field of pain management, musical characteristics such as sound intensity, tempo, timbre, and arousal level have been shown to affect ANS activity in a plethora of studies ( 62 68 ). However, only recently, audio frequencies, which constitute another inherent feature of music, have been brought into focus of scientific investigations ( 69 72 ). From a technical perspective, the term frequency describes the number of oscillations per time unit, i.e., for audio frequency, it is the number of vibrations per second that determines the pitch of a sound and is measured in Hertz (Hz).…”
Section: Introductionmentioning
confidence: 99%